Social Impacts of Modern Small-scale Mining: Case Studies from Serbia and Bosnia & Herzegovina. Issue 8 (3rd August 2022) - Sydd, O.; Sairinen, R.; Orenius, O.; Tiainen, H.
Abstract: This paper analyzes the social impacts of "modern" small-scale mining as perceived by four small communities in Serbia and Bosnia & Herzegovina. The case data consists of 58 semi-structured interviews conducted in 2017–2019. The cases represent examples of old metal mining sites from the Yugoslavian period, recently reopened for exploration and operations. The paper makes a contribution both to social impact research on mining and analysis of the social aspects of new small-scale mining development in Europe. The study revealed that respondents perceived local employment, slowing down migration, and the socio-economic development of the region as the main social impacts of mining development. The study has shown that the "scale" of mining operations is barely regarded by local residents as a determining factor in shaping their attitudes toward the impacts of small-scale mining, while the socio-economic context and historical legacy are important factors in forming social acceptance.